2023
DOI: 10.1002/aenm.202301118
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Conversion of CH4 to High Value‐Added C1 Oxygenates over Pd Loaded ZnTi‐LDH

Abstract: The selective oxidation of methane to high value‐added liquid oxygenated compounds under mild conditions is of great significance to promote the efficient utilization of the carbon source, but it also faces the dilemma of low activity and over‐oxidation. Here, ZnTi‐layered double hydroxides (LDH)‐A200 photocatalysts with Pd loading are prepared to achieve efficient oxidation of methane, with O2 as an oxidant under ambient condition. The highest generation rate of C1 liquid products (methanol and formaldehyde) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Worth noting is that Au and Pd are effective catalysts for O 2 activation and subsequent oxidation reactions, but it is challenging to accurately regulate the pathway of O 2 evolution using only monometallic catalyst. , For example, as an excellent electronic conductor, Au can promote the separation of photogenerated carriers for the O 2 reduction into *OOH and H 2 O 2 , but it has a limited ability to break O–O bond into *O and *OH. In contrast, Pd exhibits strong adsorption on the O 2 , leading to the effective cleavage of the O–O bond. And *OOH or H 2 O 2 can be easily decomposed into *O and *OH on Pd, but the strong interaction between *O and Pd may result in surface poisoning. ,, Recently, Jiang et al found that the selective formation of ROS could be regulated by adjusting the size of active sites (i.e., single atoms or nanoparticles) on the Au/In 2 O 3 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Worth noting is that Au and Pd are effective catalysts for O 2 activation and subsequent oxidation reactions, but it is challenging to accurately regulate the pathway of O 2 evolution using only monometallic catalyst. , For example, as an excellent electronic conductor, Au can promote the separation of photogenerated carriers for the O 2 reduction into *OOH and H 2 O 2 , but it has a limited ability to break O–O bond into *O and *OH. In contrast, Pd exhibits strong adsorption on the O 2 , leading to the effective cleavage of the O–O bond. And *OOH or H 2 O 2 can be easily decomposed into *O and *OH on Pd, but the strong interaction between *O and Pd may result in surface poisoning. ,, Recently, Jiang et al found that the selective formation of ROS could be regulated by adjusting the size of active sites (i.e., single atoms or nanoparticles) on the Au/In 2 O 3 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Noble metal (Pt, Au, Ag, Pd) modified photocatalysts have been widely developed for the oxidation of CH 4 into liquid oxygenates in the oxygen atmosphere, because noble metals can act as both O 2 adsorption centers and photogenerated electron capture sites for the enhancement of O 2 conversion into active oxygen species . However, O 2 is usually adsorbed in a lateral configuration on the metal nanoparticle surface, which leads to the difficulty in the release of the generated •OOH but rapidly cracks into •OH to cause the overoxidation reaction .…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of light or electricity to drive CH 4 and CO 2 conversions not only constitutes an environmentally sustainable and mild approach but also holds the potential to significantly reduce the activation barriers in thermodynamics. To date, considerable endeavors have been devoted to catalysts design for CH 4 and CO 2 conversion, encompassing methodologies such as hybridization, [15,16] alloying, [17,18] single-atom materials, [19][20][21] and other innovative approaches. Up to now, constructing single atom sites is considered an effective strategy to improve the metal utilization efficiency of catalysts for CH 4 and CO 2 conversion because a noble metal is often needed.…”
Section: Introductionmentioning
confidence: 99%